Legal Semiotics Hotel Condominium as a Property Investment Legal Practice in Indonesia - Tari, Nila; Nefi, Arman; Syanel, M. Faiz Putra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This paper examined the legal existence of condominium-hotel (“condotel”), by analyzing the existence of Property Law in Indonesia. The preparation of this paper uses a philosophical approach in legal research, by analyzing the prevailing flats regulations in Indonesia. In this case, there is no single regulation that is the legal umbrella of condotel. The implication of this is that it creates legal uncertainty for owners and parties who want to invest through condotel. In addition, Constitutional Court from Decision No. 62/2022 concerning the transformation of apartment into the condotel is the misusage of the Apartment, in addition, there is the punishment, it is could be revoke the SHMSRS as its property right. So, reform is needed in providing legal certainty for condotel. In this case, both to provide a basis for legal certainty for condotel and a prohibition on their existence in Indonesia.